Функциональные напитки как основа здорового питания - Короленко, Алина Витальевна; Тетерина, Светлана Николаевна (My University, 2014)
В настоящее время среди существующих групп функциональных продуктов наиболее стремительно завоёвывают рынок функциональные напитки. Прежде всего, напитки – это наиболее удобная и доступная форма получения необходимых для организма нутриентов. Именно напитки можно рассматривать как оптимальную и наиболее технологическую форму пищевого продукта. Nowadays, an important nutrition problem is the lack in the human ration of vitamins and certain trace elements, which causes metabolic processes disorders and, consequently, leads to the development of pathologies. Non-alcoholic beverages may become a valuable element of healthy nutrition. Since they contain a wide range of carbohydrates, organic acids, mineral substances, vitamins and other biologically active components, due to which they perform restorative effect on human body.
Keywords: функциональные напитки; здоровое питание; биологически активные вещества; ферментированные напитки; functional drinks; biologically active components; healthy meal; кафедра біотехнології і мікробіології